Relationship between obesity and depression in teenagers - Mayra Alejandra Moreno Martinez; Ma. De la Luz Martínez Aguilar; Hermelinda Ávila Alpirez; Aurora Félix Alemán; Gustavo Gutiérrez Sánchez; Tirso Duran Badillo (Cultura de los cuidados, 2018)
Objective: Determine if a relationship between obesity and depression exists in teenager from the Colegio de Bachilleres de Tamaulipas (COBAT), Matamoros, Tamaulipas 2016. Material and methods: Study, correlational and transversal. Population, 60 teenagers who presented a BMI of 30 and over, which indicates some degree of obesity. The instrument used was the Beck Depression Inventory (second revision), BDI-II. The obesity variable was classified according to the stipulated by the WHO, which are four classes: Class 1 (30.0-34.9 BMI), Class 2 (35.0-39.9 BMI), Class 3 (40.0 BMI) y Class 4 (40 and over). Results: Regarding depression level, 68.3% of the subjects normal, 20.0% light mood disturbance, 10.0% moderate depression and 1.7% severe depression. In obesity the 66.7% class one, 25.0% class two, 6.7% class three and 1.7% class four. Base on the Spearman’s Correlation test, no meaningful statistical relationship was shown between the obesity and depression variables (p = .572). Conclusion: There was no significant statistical relationship found between obesity and depression variables in the studied teenagers.